2019
DOI: 10.1016/j.mayocp.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Symptomatic Kidney Stone Recurrence After the First and Subsequent Episodes

Abstract: Objective: To predict symptomatic recurrence among community stone formers with one or more prior stone episode. Patients and Methods: A random sample of incident symptomatic kidney stone formers in Olmsted County, Minnesota were followed for all symptomatic stone episodes resulting in clinical care from 1/1/1984 to 1/31/2017. Clinical and radiographic characteristics at each stone episode predictive of subsequent episodes were identified. Results: There were 3,364 incident kidney stone formers with 4,951 epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 27 publications
6
65
0
Order By: Relevance
“…The marked difference between brushite and CaOx SF with respect to papillary and stone matrix findings is especially striking, given the fact that in this series demographic and metabolic characteristics of the 2 patient groups are so similar. Brushite stones carry a worse prognosis than CaOx stones in certain respects, as brushite stones have increased risk of recurrence, 39 are frequently large and bilateral, 40 and require more extracorporeal lithotripsy procedures 41 compared with CaOx stones. Of concern, brushite stones appear to be increasing in prevalence, 42 including among pediatric SF.…”
Section: Discussionmentioning
confidence: 99%
“…The marked difference between brushite and CaOx SF with respect to papillary and stone matrix findings is especially striking, given the fact that in this series demographic and metabolic characteristics of the 2 patient groups are so similar. Brushite stones carry a worse prognosis than CaOx stones in certain respects, as brushite stones have increased risk of recurrence, 39 are frequently large and bilateral, 40 and require more extracorporeal lithotripsy procedures 41 compared with CaOx stones. Of concern, brushite stones appear to be increasing in prevalence, 42 including among pediatric SF.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Nephrolithiasis is a disorder of mineral metabolism that is associated with increased risk for chronic kidney disease, 4,5 fracture, 6 and hypertension. 5,7 Individuals with nephrolithiasis also have a high risk for recurrent painful kidney stone events, 8,9 some of which require surgery and are associated with increased risk for kidney failure and death. 10 Due the rapid shift in the epidemiology of nephrolithiasis, investigators have focused on identifying novel determinants of kidney stone disease, including antibiotics and their impact on the intestinal and urinary microbiome composition.…”
mentioning
confidence: 99%
“…The risk of lifelong recurrence was up to 60%-80%. In a previous study, Vaughan et al [17] indicated that the stone recurrence rate was 3.4% after the rst episode, 7.1% after the second episode, 12.1% after the third episode, and 17.6% after the fourth or higher episode. Therefore, despite the fact that the standard for the outcome evaluation of residual fragments in the upper urinary tract was relied on the no residual stones after treatment [11,12], some patients may present posttreatment recurrence, which showed increase in time with the disease duration and treatment frequencies [10].…”
Section: Discussionmentioning
confidence: 94%